Growth of GaN on Patterned Sapphire Substrate with High-Index Facets. (15th October 2015) - Chang, Sheng-Chieh; Chen, Chien-Chih; Chang, Tsu-Chi; Lin, Kun-Lin; Lu, Tien-Chang; Chang, Li; Wu, YewChung Sermon
Abstract : Periodic pyramidal array patterned sapphire substrate (PSS) with various inclined facets was fabricated by wet etching. It was found that 34 ̄ 17, 41 ̄ 3 ̄ 18, and 123 ̄ 5 facets are exposed on the PSS structure after etching. GaN grown on the PSS by metal-organic chemical vapor deposition was found to have a semi-polar orientation by structural characterization with scanning and transmission electron microscopy. Also, the results show that GaN is mainly grown on the 123 ̄ 5 sapphire facet with the orientation relationship between GaN and sapphire as (011 ̄ 4 ̄ )GaN // (33 ̄ 06 ̄ )sapphire and [022 ̄ 1]GaN // [112 ̄ 0]sapphire, and the dislocation density in the grown GaN decreased with thickness. In addition, photoluminescence and catholuminescence measurements show only strong near-band-edge emission from the semi-polar GaN on the 123 ̄ 5 sapphire facet.